Effects of Cultivar and Maternal Environment on Seed Quality in Vicia sativa - Li, Rong; Chen, Lijun; Wu, Yanpei; Zhang, Rui; Baskin, Carol C.; Baskin, Jerry M.; Hu, Xiaowen (Frontiers in Plant Science, 2017)
Production of high quality seeds is of fundamental importance for successful crop production. However, knowledge of the effects of increased temperature resulting from global warming on seed quality of alpine species is limited. We investigated the effect of maternal environment on seed quality of three cultivars of the leguminous forage species Vicia sativa, giving particular attention to temperature. Plants of each cultivar were grown at 1700 and 3000 m a.s.l., and mass, germination, electrical conductivity of leakage and longevity were determined for mature seeds. Seeds of all three cultivars produced at the low elevation had a significantly lower mass and longevity but higher electrical conductivity of leachate than those produced at the high elevation, suggesting that increased temperatures decreased seed quality. However, seed viability did not differ between elevations. The effects of maternal environment on seed germination strongly depended on cultivar and germination temperature. At 10 ºC and 15 ºC, seeds of “Lanjian 3” produced at high elevation germinated to higher percentages and rates than those produced at low elevation, but the opposite trend was observed at 20ºC. However, for seeds of “Lanjian 1” and “Lanjian 2”, no significant effect of elevation was observed in germination percentage. Our results indicate that the best environment for the production of high quality seeds （e.g. high seed mass, low EC, high seed longevity） of V. sativa is one in which temperatures are relatively low during seed development.